2012
DOI: 10.1097/mcp.0b013e32834db255
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography scans in severe asthma

Abstract: Purpose of Review-Asthma is a global burden, affecting 5% of the general adult population, of whom approximately 5-10% suffer from severe asthma. Severe asthma is a complex heterogeneous disease entity, with high morbidity and mortality. Increasingly novel techniques in computerised tomography are being used to understand the pathophysiology of severe asthma. The utility and clinical implications of these CT techniques are the focus of this review.Recent Findings-Novel qualitative and quantitative CT imaging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 47 publications
0
24
1
Order By: Relevance
“…Varicose and cystic bronchial dilation were rare, and they were observed mainly in the patients with the most severe asthma, while cylindrical bronchiectasis could be found in nearly all asthmatic patients (14,15). Some investigators reported that bronchial dilation was correlated with disease severity in asthma, FEV 1 , and duration of asthma (15,30,44,45), and contributed to disease severity and difficulty of asthma control (42) but other studies haven't found this correlation (14,28,40,41). Bronchial dilation is an irreversible change due to bronchial wall weakening and increased pressure in airways.…”
Section: Discussionmentioning
confidence: 99%
“…Varicose and cystic bronchial dilation were rare, and they were observed mainly in the patients with the most severe asthma, while cylindrical bronchiectasis could be found in nearly all asthmatic patients (14,15). Some investigators reported that bronchial dilation was correlated with disease severity in asthma, FEV 1 , and duration of asthma (15,30,44,45), and contributed to disease severity and difficulty of asthma control (42) but other studies haven't found this correlation (14,28,40,41). Bronchial dilation is an irreversible change due to bronchial wall weakening and increased pressure in airways.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inflammation and remodeling in this compartment can be detrimental to SA patients, as some reports suggest asthma severity increases in proportion to the involvement of the distal lung (191,192). Unfortunately, most data on the distal lung in asthma provide little to no histological information or association with computed tomographic assessments of air trapping and regional ventilation/perfusion (193), exhaled gases (nitric oxide) (194), or physiological measures (195). Alternatively, autopsy distal lung tissue from fatal asthma specimens often has limited associated clinical information (138).…”
Section: Distal Lung Pathology: Small Airways and Alveolimentioning
confidence: 95%
“…These imaging tools enable the visualization of regional functional impairment in asthmatic lungs, and may facilitates the early diagnosis, asthma phenotyping, the monitoring of disease progress, the assessment of treatment effect and the planning of targeted therapies [6][7][8]. Most previous work has focused on a component of lung function, such as ventilation, perfusion, or ventilation-perfusion mismatch.…”
Section: Introductionmentioning
confidence: 99%